2015
DOI: 10.1007/s11238-015-9525-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive ability and the effect of strategic uncertainty

Abstract: Abstract:How is one's cognitive ability related to the way one responds to strategic uncertainty? We address this question by conducting a set of experiments in simple 2 x 2 dominance solvable coordination games. Our experiments involve two main treatments: one in which two human subjects interact, and another in which one human subject interacts with a computer program whose behavior is known. By making the behavior of the computer perfectly predictable, the latter treatment eliminates strategic uncertainty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 46 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…The incentives of player Bs, in turn, go in the opposite direction: the gain from using the dominant strategy r (and conditional on player As' choice R ) is lower in Game 1 [with payoff increasing from 4.75 to 5 between ( R, l ) and ( R, r )] than in Game 2 (where payoff increases from 8.5 to 10). In line with Jacquemet and Zylbersztejn ( 2014 ) and Hanaki et al ( 2016 ) (who report that both players only react to their own monetary incentives) and as discussed in Section 3.1, each of these games generates sizable yet diverse empirical violations of dominance solvability. These two games together thus provide a wide range of monetary incentives to use dominance solvability within a common strategic environment 9 .…”
Section: Experimental Designsupporting
confidence: 70%
See 2 more Smart Citations
“…The incentives of player Bs, in turn, go in the opposite direction: the gain from using the dominant strategy r (and conditional on player As' choice R ) is lower in Game 1 [with payoff increasing from 4.75 to 5 between ( R, l ) and ( R, r )] than in Game 2 (where payoff increases from 8.5 to 10). In line with Jacquemet and Zylbersztejn ( 2014 ) and Hanaki et al ( 2016 ) (who report that both players only react to their own monetary incentives) and as discussed in Section 3.1, each of these games generates sizable yet diverse empirical violations of dominance solvability. These two games together thus provide a wide range of monetary incentives to use dominance solvability within a common strategic environment 9 .…”
Section: Experimental Designsupporting
confidence: 70%
“…Each of the four resulting experimental treatments is implemented through a between-subject procedure—each subject participates in only one experimental condition. This data come from a large dataset, part of which has been previously used by Hanaki et al ( 2016 ). The main focus of that study is player As' behavior under strategic uncertainty and its relation to monetary incentives and fluid intelligence.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from experimental economics literature on strategic thinking suggests that the cost of learning in interactive settings varies with fluid intelligence 35 – 40 . Studies in cultural evolution literature find a variation in social learning strategies that depends on social group and individual characteristics 13 , 32 , 41 , 42 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (Dequech, 2001;Hanaki, Jacquemet, Luchini, & Zylbersztejn, 2015) has widely confirmed that sensitivity to uncertainties has a prevalent impact on the rationality of choicemaking. Individuals sometimes avoid risk and sometimes seek it.…”
Section: Uncertaintiesmentioning
confidence: 90%